GAS CHROMATOGRAPHY-MASS SPECTROSCOPY STUDIES ON CESTRUM NOCTURNUM MACERATED METHANOLIC EXTRACT - Chaskar, Pratip Kashinath; Tank, Shivali Hargovind; Doshi, Gaurav Mahesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Phytochemical screening has revealed the presence of alkaloids, glycosides, carbohydrates, steroids, flavonoids, saponins, and tannins from methanolic extract of Cestrum nocturnum. In this research, we have identified and confirmed the structures of the constituents by gas chromatography– mass spectrometry (GC-MS) from the methanolic extract of C. nocturnum leaves. Methods: Shade-dried leaves were powdered and extracted with methanol by cold extraction procedures and the crude extract obtained was used for GC-MS. Results: There were total five components prominently eluted from C. nocturnum extract, viz., ethyl citrate, phytol, 4-isobutylmorpholine, n-hexadecanoic acid, and α-amyrin. Conclusion: GC-MS studies helped to recognize the phytochemical constituents based on their retention time and verification of MS libraries. In future, C. nocturnum leaves may be subjected to different extraction procedures and number of elucidating phytoconstituents can be studied for their ethnopharmacological relevance citing the literature. Keywords: Cestrum nocturnum, Gas chromatography-mass spectroscopy, α-Amyrin, n-Hexadecanoic acid, Ethyl citrate, Phytol, 4-Isobutylmorpholine.